Characteristics of Relative Deprivation of Disadvantaged Children In School Setting - Euis Nurhidayati; Sunaryo Kartadinata; M Solehuddin; Syamsu Yusuf (Universitas Ahmad Dahlan, 2020)
Relative deficiencies develop in two types of society: poor (deprived) and disadvantaged (unfortunate), little research for this arrangement has been conducted in the field of education. This will discuss the relative deprivation character of underprivileged children in the realm of education. This research uses a descriptive method. The descriptive survey was used to describe the relative character of deprivation among underprivileged children at school, knowing the differences between boys and girls. The subjects in this study were grade 5 and grade 6 elementary school students in the Bekasi area with a total of 77 students: 37 boys and 40 girls. The instrument used in this study is an instrument that has been tested by experts, validity and reliability. It uses a relative deprivation scale for disadvantaged children. The data were analyzed descriptively by describing the minimum and maximum scores of each item, thus showing strength of each characteristic. In addition, the frequency score also described to highlight differences in the relative characteristics of deprivation among male and female students. The results explained that the participants had a very strong deprivation character, males were more dominant than females. The strongest characters reflected their lesser curiosity about things, but the girls exhibit better score related to rule obedience. The results of this study could be used as a reference to treat students' relative deficiencies throughÂ guidance and counseling services.